Fatigue fracture in the presence of shot peening residual stresses: initiation, propagation and relaxation phenomena - Hammond, D. W. (Cranfield University, 1988)
This thesis describes both experimental and theoretical work performed in order to analyse fatigue fracture in the presence of shot-peening induced residual stresses. In the study, four contrasting alloys were examined by fatigue testing and use was made of different test techniques to illustrate some of the phenomena associated with fatigue fracture in shot-peened components. The results demonstrate that in order to characterise the process of fatigue in a component bearing residual stresses, it is necessary to consider three groups of variables. These are the applied and residual stress state, the geometry of the component and the flaws it contains and the nature of the alloy itself, including any propensity to work harden, recover or undergo phase changes due to peening or fatigue loading.